Seborrhoeic keratosis with autosomal dominant inheritance - a rare case report - Shariff, V. N. S. Ahamed; Balamurugan, L.; Saravanan, N. (International Journal of Research in Medical Sciences, 2017)
Seborrhoeic keratosis is a benign tumour composed of epidermal keratinocytes, displaying varying morphological features, frequently pigmented and more common in the elderly. Various clinical and histopathological variants have been described. A genetically determined predisposition to Seborrhoeic keratosis is largely accepted. We report a case of multiple Seborrhoeic keratoses of childhood onset and transmitted for three generations in her family members as an autosomal dominant trait.